Relative bradycardia presented as a clinical feature of Brucella melitensis infection: A case report - Huang, Kai; Yu, Xuxia; Yu, Yushan; Cen, Yin; Shu, Jie; Yang, Naibin; Chu, Jinguo (Frontiers in Medicine, 2022)
Brucellosis, caused by Brucella species, is an infectious disease transmitted by contacting with infected animals or their secretions. It is characterized by fever and headache. Relative bradycardia is sinus bradycardia as a phenomenon of dissociation between heart rate and body temperature, insufficient increase in pulse despite high fever. We report one Chinese case of Brucella melitensis infection with relative bradycardia as a condition but no significant compensatory increase in heart rate despite high fever. This is the first report of relative bradycardia among Brucellosis.